PERLINDUNGAN PELAKU USAHA TERHADAP PEMBATALAN OLEH KONSUMEN E-COMMERCE DALAM SISTEMPEMBAYARAN CASH ON DELIVERY - Anindya Putri (2022)
By using normative juridical research methods, this study will discuss the payment system for e-commerce transactions between consumers and business actors as well as protection for business actors if consumers cancel e-commerce transactions in the cash on delivery payment system. The purpose of this study is to explain the payment system between consumers and business actors in e-commerce transactions and to analyze the protection for business actors in the event of cancellation of e-commerce consumer transactions in the cash on delivery system. With the birth of buying and selling transactions through online media or online on e-commerce sites, giving consumers the freedom to choose the various payment systems provided, such as bank transfers, debit/credit cards, through mini markets, and also cash on delivery (COD). . Cash on delivery is a payment method that is currently being used in buying and selling goods, where payments are made after the goods are delivered and received by consumers. However, it is often found that acts of default committed by consumers to business actors are often found. The results found from this study are that (1) The cash on delivery payment system is recognized as an electronic transaction system in accordance with the applicable laws and regulations. (2) Protection of business actors against incurring losses due to default acts committed by consumers in the cash on delivery payment payment system, i.e. business actors can file lawsuits in court or out of court. Keyword: Business Actor Protection, Breach, Cash On Delivery, E- commerce, Online Transaction.